2020
DOI: 10.1002/cem.3298
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality reduction of multielement glass evidence to calculate likelihood ratios

Abstract: Dimensionality reduction of multivariate elemental concentrations of glass is reported for computing likelihood ratios (LRs). The LRs calculated using principal component analysis (PCA) and a post hoc calibration steps result in very low (<1%) false inclusions when comparing glass samples known to originate from different sources and very low (<1%) false exclusions when comparing glass samples known to originate from the same source. The LRs calculated using the novel PCA approach are compared with previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a follow‐up study, Gupta et al investigated the use of PCA for dimensionality reduction of multivariate elemental concentrations of glass for computing likelihood ratios and compared it to the multivariate kernel‐PVA calibration previously reported. The PCA‐LR approach resulted in low false exclusion and inclusion rates (<1%) while being less computationally intensive than the MVK‐PVA (Gupta et al, 2021).…”
Section: The Current State Of Methodologies For Forensic Glass Examin...mentioning
confidence: 99%
“…In a follow‐up study, Gupta et al investigated the use of PCA for dimensionality reduction of multivariate elemental concentrations of glass for computing likelihood ratios and compared it to the multivariate kernel‐PVA calibration previously reported. The PCA‐LR approach resulted in low false exclusion and inclusion rates (<1%) while being less computationally intensive than the MVK‐PVA (Gupta et al, 2021).…”
Section: The Current State Of Methodologies For Forensic Glass Examin...mentioning
confidence: 99%
“…The BKA typically analyzes the following 18 elements: 7 Li, 23 Na, 25 Mg, 27 Al, 39 K, 42 Ca, 49 Ti, 55 Mn, 57 Fe, 85 Rb, 88 Sr, 90 Zr, 137 Ba, 139 La, 140 Ce,…”
Section: Databasesmentioning
confidence: 99%
“…The need of more databases to train the models, as it happens in score-based approaches, exacerbates the problem. These data requirements also appear when using principal component analysis (PCA) [27] or other dimensionality reduction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [ 189 ] reported on the use of a novel dimensionality reduction method to calculate likelihood ratios (LRs) from multivariate elemental concentrations of glass using LA-ICP-MS data. The LRs were calculated using principal component analysis (PCA) and post hoc calibration steps resulting in very low (<1%) false inclusions when comparing glass samples known to originate from different sources and very low (<1%) false exclusions when comparing glass samples known to originate from the same source.…”
Section: Introductionmentioning
confidence: 99%